Analisis Perubahan kV dan mAs terhadap Kualitas Gambar dan Dosis Radiasi pada Pemeriksaan Multislice Computed Tomography Abdomen dalam Kasus Tumor Abdomen di Instalasi Radiologi RSUD dr. Saiful Anwar Malang - Ardi Soesilo Wibowo; Gatot Murti Wibowo; Anang Prabowo (Jurnal Imejing Diagnostik (JImeD), 2016)
Backgroud: Examination of the abdomen CT scan is often done by using standard protocol, meanwhile the actual parameter can be modified according to local needs considering image quality and radiation dose based on Karabulut and Ariyuek (2016). Abdomen CT Scan by GE 16 slices unit in Radiology Instaallation of Dr. Saiful Anwar Malang Hospital, using exposure factor of 120 kV, 234 mAs and the value of the CTDI dose was 53.04 mGy. While the BAPETEN’s reference of CTDI value, a CT scan of abdomen was 25 mGy.  This study aims to determine the changes of the value of kV and mAs to the image quality and the radiaton dose in the abdomen MSCT examination on abdominal tumor case in Radiology Installation of Dr. Saiful Anwar Malang Hospital.Methods: This research was a quantitative research with an experimental approach. The data were collected from three variations of tube voltage (kV) ie 100 kV, 120 kV and 140 kV and three variations of tube current value and time (mAs) ie, 180 mAs, 195 mAs, and 210 mAs. Radiographs was evaluated by three radiology physicians. Data were analyzed by scoring method of respondent’s assessment to assess MSCT image quality of abdominal tumor, while the radiation dose was obtained by CTDI recording.Results: The results showed that there was influence of tube voltage variation to image quality of abdominal tumor using MSCT unit. The higher kV used, the higher image quality resulted. From the calculation of the percentage from the assessment, the highest score of variation was at 140 kV, while the lowest score of variation was at 100 kV. Based on the recording CTDI radiation dose on the monitor, found that the higher value of kV, the higher radiation resulted. The mAs variations influenced the image quality of abdominal tumor using MSCT unit. Acoording to the percentage of the assessment, the highest score of variation found in 210 mAs, and the lowest score of variation found in 180 mAs. Based on the recording of radiation dose on the monitor, the higher mAs value, the higher radiation dose using MSCT unit. It was recommended to use 195 kV and 120 mAs for MSCT examination of abdominal tumor in Radiology Installation of Dr. Saiful Anwar Malang Hospital.Conclusion: There was influence of kV and mAs variation to anatomical image clarity and radiation dose of abdomen MSCT examination